Exploring the effects of emotional design and emotional intelligence in multimedia-based learning: an engineering educational perspective. Issue 1 (3rd April 2019) - Kumar, Jeya Amantha; Muniandy, Balakrishnan; Wan Yahaya, Wan Ahmad Jaafar
ABSTRACT: Emotions are an important aspect in learning and with the current boom in instructional technology, researchers are exploring methods to investigate how emotions may be manipulated to positively influence online learning. One such method is by adapting the theory of emotional design through multimedia elements. This theory emphasises on individuality and metacognition in exploring these learning outcomes and by this we choose to explore the effects of emotional intelligence (EI). We replicated the methodology used in previous research studies in emotional design in multimedia learning by further exploring the gaps from those studies especially the effects of negative design, EI and a new sample that primarily focusses on engineering undergraduates in Malaysia. This study was designed as a quantitative quasi-experimental using a 3 × 2 factorial design. Based on the findings, it was found that emotional design is a better predictor of cognitive outcomes, whereas EI was a better predictor of emotional outcomes such as motivation and satisfaction for multimedia-based learning. It was also found that positive and negative designs have similar effects on students' learning outcomes, while EI affected perceived satisfaction in each design.